Dental implant register: Summary and consensus statements of group 2. The 5th EAO Consensus Conference 2018. (10th October 2018) - Klinge, Björn; Sanz, Mariano; Alcoforado, Gil; Bienz, Stefan P.; Cosyn, Jan; De Bruyn, Hugo; Derks, Jan; Figuero, Elena; Gurzawska, Katarzyna; Heitz‐Mayfield, Lisa; Jung, Ronald E.; Ornekul, Turker; et al.
Abstract: Objectives: This publication reports the EAO Workshop group‐2 and consensus plenary discussions and statements on a narrative review providing the background and possible facilities and importance of a dental implant register, to allow for a systematic follow‐up of the clinical outcome of dental implant treatment in various clinical settings. It should be observed that the format of the review and the subsequent consensus report consciously departs from conventional consensus publications and reports. Material and methods: The publication was a narrative review on the presence and significance of quality registers regarding select medical conditions and procedures. The group discussed and evaluated the publication and made corrections and recommendations to the authors and agreed on the statements and recommendations described in this consensus report. Results: Possible registrations to be included in an implant register were discussed and agreed as a preliminary basis for further development, meaning that additional parameters be included or some be deleted. Conclusions: It was agreed to bring the idea of an implant quality register, including the presented results of discussions and proposals by the group‐ and plenary sessions, to the EAO Board for further discussion and decision.